Plan de negocio para la creación de un centro de asistencia integral al adulto mayor en la ciudad de Guaranda, 2023. - Escobar Jarrín, Lenin Fernando (2023)
The increase in life expectancy worldwide has led to a notable growth in the elderly population, especially in low and middle-income countries. These demographic changes have highlighted the need for proper services and care for this population. The main goal of this study was to analyze the feasibility of setting up an Integral Care Center for the elderly in the city of Guaranda during the 2023 period. To achieve this aim, a market study was conducted evaluating the supply and demand for care services, and technical, operational, and financial aspects for the center's creation were analyzed. The research adopted a quantitative approach, gathering data through surveys and analyzing relevant information from secondary sources. A growing demand for specialized elderly care services in Guaranda was found. Although gerontological centers exist in the province, there is an insufficient supply that does not meet the projected demand. The creation of the Integral Care Center "SPA Abuelitos de Guaranda" was considered technically possible and economically profitable, supported by positive economic indicators. Given the unmet demand and showed viability, the establishment of the proposed center is recommended, which, besides being a solid investment, will address the crucial needs of the elderly population in Guaranda.